2005
DOI: 10.1248/yakushi.125.177
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dose of Mycophenolate Mofetil and the Occurrence of Cytomegalovirus Infection and Diarrhea in Renal Transplant Recipients

Abstract: To establish guidelines for avoiding the side eŠects of mycophenolate mofetil (MMF) in renal transplant recipients with tacrolimus (TAC)-based immunosuppression, the relationship between the daily dose of MMF and the occurrence of side eŠects was analyzed in this study. The frequency of side eŠects was investigated retrospectively in 28 renal transplant recipients treated with immunosuppression (men 14 : women 14, age: 33.0 ± 12.4 years, weight: 50.9 ± 10.7 kg). Cytomegalovirus (CMV) infection and diarrhea wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Though, some studies [6,17] have also shown higher, but not statistically significant percentage of leucopenia with Azathioprine use when compared to MMF (2 g/day) in patients who developed CMV disease in their cohort. Only higher dose of MMF (3 g/day) was associated with an increased incidence of leucopenia in patients who developed CMV disease when compared with Azathioprine [10,12,18].…”
Section: Discussionmentioning
confidence: 94%
“…Though, some studies [6,17] have also shown higher, but not statistically significant percentage of leucopenia with Azathioprine use when compared to MMF (2 g/day) in patients who developed CMV disease in their cohort. Only higher dose of MMF (3 g/day) was associated with an increased incidence of leucopenia in patients who developed CMV disease when compared with Azathioprine [10,12,18].…”
Section: Discussionmentioning
confidence: 94%
“…[33] showed an increased metabolic ratio of MPAG/MPA in patients under CsA, which is caused by an inhibition of the biliary excretion of MPAG under CsA. Therefore, patients taking tacrolimus might have a bigger exposure of their gut toward MPA and this could explain the higher rate of gastrointestinal side effects under therapy with tacrolimus and MPA [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea occurs more frequently as an adverse effect of MMF in patients treated with TAC. [27][28][29] We suggest that estimating biliary excretion of MPAG is needed to avoid the risk of intestinal injury in combination therapy with TAC during the maintenance period.…”
Section: Discussionmentioning
confidence: 99%